The effects of the COVID-19 pandemic on the physical activity of the Thai population: Evidence from Thailand's Surveillance on Physical Activity 2020 - Piyawat Katewongsa; Dyah Anantalia Widyastari; Pairoj Saonuam; Narumol Haemathulin; Narakorn Wongsingha (Elsevier, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has undoubtedly disrupted the physical activity (PA) of the Thai population. This study examined the effect of the COVID-19 pandemic on moderate-to-vigorous PA (MVPA) of Thai adults and assessed the effects of the national curfew policy and health-promotion campaigns on influencing PA during the pandemic. Methods: Thailand's Surveillance on Physical Activity (SPA) 2019 and 2020 datasets were employed to compare the PA level of Thai adults aged 18-64 years before and during the COVID-19 pandemic. Samples of 4460 respondents from SPA 2019 and 4482 respondents from SPA 2020 were included in the analysis. Global Physical Activity Questionnaires (Version 2.0), were used to measure PA in both periods. Sufficient MVPA for adults was defined based on the recommendation of 75 min of vigorous PA or a combination of 150 min of MVPA per week. Results: The proportion of Thai adults who had sufficient MVPA declined from 74.6% before the pandemic to 54.7% during the pandemic, and that decline was accompanied by a reduction in the cumulative minutes of MVPA from 580 min to 420 min. During the COVID-19 pandemic, male and middle-aged individuals were 1.3 times and 1.2 times more likely to have sufficient MVPA, respectively. Those who were unemployed, resided in an urban area, and/or had chronic disease(s) were 27%, 13%, and 27% less likely to meet the recommended level of PA during the pandemic, respectively. Those who were exposed to the Fit from Home campaign were 1.5 times more likely to have sufficient MVPA. Conclusion: The pandemic measures imposed by the government have reduced the cumulative min of work-related PA, transportation PA, and recreational PA and have slowed Thailand's progress toward its PA goals. Although the Fit from Home campaign has probably contributed to a slight increase in MVPA, it will take some time for Thais to return to the pre-COVID-19 level of PA. Health promotion messages need to be continuously delivered to reduce irrational fear of infection and to boost the PA level of the Thai population as a health-promoting intervention.